Pendekatan Non Penal Dalam Penanggulangan Kekerasan Seksual Verbal Anak - Lawalata, Kevin Izaac Enrique; Hehanussa, Deassy Jacomina Anthoneta; Wadjo, Hadibah Zachra (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: Child verbal sexual crimes are still a serious problem and this is a social disaster that worries society. This condition demands the protection of children.Purposes of the Research:  This study aims to analyze and discuss whether the non-penal approach is effective in dealing with child verbal sexual violence and what non-penal approaches can be used in tackling child verbal sexual violence.Methods of the Research:  The research method used is an empirical juridical research type. The research locations are the Gasira Maluku Foundation, Ambon 1 Public High School, Ambon 4 State Vocational School and the National Commission on Human Rights. Polulation, research samples of Gasira assistant staff, counseling teachers at SMA Negeri 1 Ambon, counseling teachers at SMK Negeri 4 Ambon and Komnas HAM analyst staff. Data collection through observation and interviews. Data processing and data analysis using qualitative methods.Results of the Research: The results of the study show that the non-penal approach is not yet effective in tackling child verbal sexual violence. This is because children's verbal sexual violence still occurs in schools and in society and is considered something that is normal or usually done to children. Even though verbal sexual violence is sexual violence that is carried out in a non-physical form against children, which is related to parts of the child's body and is related to sexual desire, resulting in intimidation, humiliation, humiliation, or embarrassment. Besides that, the lack of knowledge of school children, parents and the community regarding verbal sexual violence because they do not know what forms, impacts and non-penal approaches and penal approaches in dealing with child verbal sexual violence include. Forms of a non-penal approach that can be used in tackling child verbal sexual violence, namely conducting training, outreach to children and providing counseling and social education in order to develop sensitivity and social awareness of the community regarding the impacts that can arise from acts of child verbal sexual violence, the formation of the individual character of a group or community by providing moral education, religious education and handling child verbal sexual violence by the school and in the community through reprimands and advice to perpetrators not to commit violence and assistance to children as victims of verbal sexual violence.